Discursive tensions, desacralization and migration in the Peruvian poetry of the 80’s - Gonzales Fernández, Guissela (2018)
In this essay we analyze the works of Odi Gonzales and Boris Espezua, authors whose poetics come from a remarkable predominance of elements belonging to the Andean imaginary. This special feature generates tensions at the discursive and epistemological level of their texts. This characteristic makes their poetics become peculiar, taking distance from the aesthetic and literary paradigms developed in Lima, the Peruvian capital city during the 80’s. The analysis of the texts will focus on those geocultural marks that show the continuity of the Andean imaginary, providing alternate ways of making poetry, and understanding what is poetic.